Investigation of Electrical Signals Transmission through Light-Induced Conductive Channels on the Surface of CdS Single Crystal - Artur O. Boikynia; Nikita S. Tkachenko; Yuriy V. Didenko; Ostap O. Oliinyk; Dmitry D. Tatarchuk (Mìkrosistemi, Elektronìka ta Akustika)
Further development of information technologies hinges on innovations in the electronic components sector, particularly in enhancing electronic communication devices. This involves creating dynamic interconnects—electrically conductive channels that can be configured on-demand within chip circuitry to overcome the "tyranny of interconnects," which limits electronic systems due to the fixed nature of conventional interconnects.